AESTHETIC RESPONSES IN 'AL-FIL AL-AZRAQ' NOVEL-TO-MOVIE ADAPTATION (RESPON ESTETIS DALAM ADAPTASI NOVEL-FILM 'AL-FIL AL-AZRAQ') - Ahmad Naufal Dzulfaroh (Leksema: Jurnal Bahasa dan Sastra, 2018)
Adaptation, as one form of response to literary texts, is a matter that has been much discussed in the world of literature or the world of art in general. An interesting case of adaptation is the adaptation of al-Fil al-Azraq's novel to a film showing the effort of an adapter to preserve the novel story as well as transforming it into a new work with a variety of creativity in it. This study aims to reveal the individuality, effects, and meaning of the text contained in the novel al-FÄ«l al-Azraq as the background text and the film al-FÄ«l al-Azraq as a foreground work as well as the media changes occurring in the adaptation work . To see this process of adaptation, the theory of aesthetic response from Wolfgeng Iser. The results of this study indicate that the adapters do dialectic with the source text and then display it in their adaptation work through changes in the text in the form of allusions, negations, and blank filling. These changes also affect the individuality, effects, and meaning of the adaptation work to the point of shifting from the source text. This shows that the work of adaptation is a new work that has its own individuality and creativity, a work of repetition without replication.